Pervasive Gaming: Formats, Rules, And Space - Bo Kampmann Walther (Fibreculture Journal, 2006)
Pervasive Gaming (PG) denotes a noteworthy change in the history and nature of computer games. By intentionally merging virtual and physical space, pervasive gaming not only extends the magic circle of play; it further challenges our conception of game rules, game mechanics, and game entities. This paper introduces and discusses some of the key characteristics of this novel trend in computer games. Following a short description of the significant features of pervasive computing, Walther explicates pervasive gaming in relation to time, space, and presence (or immersion). Then I position four axes or zones of pervasive gaming: mobility, distribution, persistence, and transmediality. Further, I describe and analyse three essential units of PG (rules, entities, and mechanics), and finally, I speculate about the role of space in PG by differentiating between tangible space, information space, and accessibility space.